Mechanisms of maintaining high suspended sediment concentration over tide-dominated offshore shoals in the southern Yellow Sea. (15th May 2017) - Xiong, Jilian; Wang, Xiao Hua; Wang, Ya Ping; Chen, Jingdong; Shi, Benwei; Gao, Jianhua; Yang, Yang; Yu, Qian; Li, Mingliang; Yang, Lei; Gong, Xulong
Abstract: An understanding of the dynamics and behaviors of suspended sediments is vital in analysis of morphological, environmental, and ecological processes occurring in coastal marine environments. To study the mechanisms of maintaining high suspended sediment concentrations (SSCs) on a tide-dominated offshore shoal, we measured water depths, current velocities, SSCs, wave parameters and bottom sediment compositions in the southern Yellow Sea. These data were then used to calculate bottom shear stresses generated by currents ( τ c ), waves ( τ w ), and wave–current interactions ( τ cw ). SSCs time series exhibited strong quarter-diurnal peaks during spring tides, in contrast to the semidiurnal signal during neap tides. A Fourier analysis showed that suspended sediment variations within tidal cycles was mainly controlled by resuspension in most stations. There existed relatively stable background SSCs (maintaining high SSCs among tidal cycles) values at all four stations during both windy (wind speed > 9.0 m/s) and normal weather conditions (wind speed < 3.0 m/s). The background SSCs had strong relationship with spring/neap-averaged τ cw, indicating background SSCs were mainly controlled by mean bottom shear stress, with a minimum value of 0.21 N/m 2 . On account of the strong tidal currents, background SSCs of spring tides were greater than that of neap tides. In addition, on the base of wavelet, statistics analyses and turbulence dissipation parameter, background SSCs during slack tide in the study area may be maintained by intermittent turbulence events induced by a combined tidal current and wave action. Highlights: Suspended sediment transport was mainly controlled by resuspension. Advection and sediment supply can also influence sediment dynamics. Resuspension was more dependent on tidal current than advection. Background SSCs was strongly related to mean bottom shear stress. Slack-tide SSCs could be maintained by intermittent turbulence events.